Whole-Genome Sequence of the Anaerobic Isosaccharinic Acid Degrading Isolate, Macellibacteroides fermentans Strain HH-ZS. (16th August 2017) - Rout, Simon P.; Salah, Zohier B.; Charles, Christopher J.; Humphreys, Paul N.
Abstract: The ability of micro-organisms to degrade isosaccharinic acids (ISAs) while tolerating hyperalkaline conditions is pivotal to our understanding of the biogeochemistry associated within these environs, but also in scenarios pertaining to the cementitious disposal of radioactive wastes. An alkalitolerant, ISA degrading micro-organism was isolated from the hyperalkaline soils resulting from lime depositions. Here, we report the first whole-genome sequence, ISA degradation profile and carbohydrate preoteome of a Macellibacteroides fermentans strain HH-ZS, 4.08 Mb in size, coding 3, 241 proteins, 64 tRNA, and 1 rRNA.